Nicaragua’s Newly Ratified Military Pact With Russia Will Likely Prompt More US Meddling - Korybko, Andrew (Andrew Korybko's Newsletter, 2026)
The form that this takes remains to be seen since the last eight years of sanctions didn’t lead to the US’ envisaged political changes.